A Proposed Paradigm for the Requirements for Designing and Using Digital Games-Based Learning by Educable Intellectual Disabled Children - Saleh, Magda; Battisha, Marwa (Technium Social Sciences Journal, 2021)
This study aims to shed further light on how to utilize digital games in education as a contribution to developing educable intellectual disabled children's teaching and learning practices via identifying the requirements for their design and use at those children's classes. Notably, the researchers focused on using digital games in promoting educable intellectual disabled children's learning experiences highlighting their different practical mechanisms and teaching practices based on literature review. Also, types of digital games capable of fulfilling the teaching requirements of those children were identified by making a list of the requirements for designing and using digital games-based learning at educable intellectual disabled children's classes consisting of 38 various requirements divided into 3 major dimensions, namely: (1) educational requirements for using digital games-based learning; (2) instructional design requirements for using digital games-based learning; and (3) practical application requirements for using digital games-based learning. Then, the proposed list was applied to a sample consisting of 25 faculty members at 5 Egyptian universities. Following data statistical analysis, it was revealed that the questionnaire total mean score is 2.73 with a relative weight of 90.1%. In a nutshell, such values verify that the questionnaire all proposed requirements are, indeed, very important for using digital games-based learning at educable intellectual disabled children's classes.